2015
DOI: 10.14202/vetworld.2015.372-381
|View full text |Cite
|
Sign up to set email alerts
|

Patho-epidemiological study on Genotype-XIII Newcastle disease virus infection in commercial vaccinated layer farms

Abstract: Aim:The present research work was carried out to study the patho-epidemiological aspects of Genotype-XIII Newcastle disease virus (NDV) infection in commercial layer in and around Anand, Gujarat. As the outbreaks have reported in vaccinated flocks, it was felt necessary to study the disease with respect to its changing pathogenicity and relevant aspects.Materials and Methods:The study comprised of patho-epidemiology of Newcastle disease (ND) by information collected from different layer farms suffering from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
5
8
0
1
Order By: Relevance
“…Based on our results, it may be suggested that the effect of Se on the immune response depends on the type of antigen with which the bird is challenged. Still, it should be noted that the antibody response, even to a particular antigen, can be influenced by the dose, route and schedule of immunisation, as well as the age, sex and immune status of the flock (Khorajiya et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, it may be suggested that the effect of Se on the immune response depends on the type of antigen with which the bird is challenged. Still, it should be noted that the antibody response, even to a particular antigen, can be influenced by the dose, route and schedule of immunisation, as well as the age, sex and immune status of the flock (Khorajiya et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The recommended strategy for the prevention of the disease is by using killed or live attenuated vaccines. Vaccination failure is a common problem and has been reported from places where the velogenic strains of NDV are endemic [10,39,40]. An alternative to this problem is the use of antiviral drugs against NDV, which is not commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…Hence proper vaccination and vaccination strategies need to be formulated to control this virus. Miller et al (2015) characterized recent vNDV isolates from Pakistan, Israel and Indonesia, and suggested that the fifth panzootic may be caused by new vNDV sub-genotype (VIIi, the available live and attenuated vaccines in India induce limited immunity and subsequently limited protection in flocks against genotype XIII; Khorajiya et al, 2015).…”
Section: Discussionmentioning
confidence: 99%